Formulasi Sediaan Krim Pelembab Ekstrak Air Buah Pepaya (Carica Papaya L.) - Ningsih, Kadek Sri Utami; Darsono, Farida Lanawati; Wijaya, Sumi (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2019)
Sucrose in papaya fruit was used as a moisturizer because it has worked as humectants, which reduce water evaporation on the surface of the skin. The purpose of this research was to determine the effect of the increasing concentrations of water extract of papaya fruit to evaluate its physical quality, effectiveness, safety, acceptability, and stability of the moisturizing cream water extract of papaya (Carica papaya L.). In this study, it used 3 formulas containing the extract of papaya fruit at concentration of 10% (formula 1), 20% (formula 2), 30% (formula 3), also blank containing base only, and base without extract and without moisturizing agent. The physical quality tests include organoleptic, pH, viscosity test, emulsion type test, dispersive power test, homogeneity, water washed power and adhesion test. The effectiveness of mouisturizer effect on the skin was tested with in vitro method: Sorption Desorption Test. Savety testing include irritation test and acceptability test. The data was analyzed using oneway ANOVA then continued with post hoc Tukey. The results showed that the increasing concentrations of the extract provides significant effect on efectivity, wherein the greater the concentration of water extract of papaya fruit (Carica papaya L.) were added, then the higher the ability to moisturize the skin and produce of moisturizer cream with pH test 6.04, viscosity 159710 cps, dispersive power 3.63 cm, water washed power 13.48 ml, adhesion 6005 second, and moisturizer cream stable during storage. The best formula is the formula 3 with a concentration extract of 30%.